2022
DOI: 10.1111/aphw.12326
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐affective responses to online positive‐psychological interventions: The effects of optimistic, grateful, and self‐compassionate writing

Abstract: Growing evidence suggests that online positivepsychological interventions effectively increase wellbeing, and a wealth of evidence describes cognitiveaffective responses to such interventions. Few studies, however, have directly compared responses across popular exercises such as the best-possible-self interven-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Individuals with high gratitude level tend to have more positive emotional experience (Ma et al, 2022 ). Study of positive emotion interventions found that 425 Germany adults who wrote thank-you notes had higher levels of gratitude, more positive self-related thoughts, and more positive emotions (Heekerens et al, 2022 ). Increasing an individual 's level of gratitude can also ease stress, get quality sleep, and have healthier social functions (Halberstadt et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with high gratitude level tend to have more positive emotional experience (Ma et al, 2022 ). Study of positive emotion interventions found that 425 Germany adults who wrote thank-you notes had higher levels of gratitude, more positive self-related thoughts, and more positive emotions (Heekerens et al, 2022 ). Increasing an individual 's level of gratitude can also ease stress, get quality sleep, and have healthier social functions (Halberstadt et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Writing sessions were carried out without any time constraints in 10 studies (e.g., Kreemers et al 2019, Leary et al 2007) since there were no separate instructions regarding the writing time. Some studies provided more flexible instructions related to time such as "maximum 30 minutes" (Sherman et al 2019), "8-10 minutes" (Odou and Brinker 2014), or "at least 15 minutes" (Heekerens et al 2022). When the interventions are examined, it is seen that the shortest intervention is 3 minutes in a single session (Moffitt et al 2018), and the longest intervention is writing for 15-20 minutes every day for 2 weeks (Kelly and Waring 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect considered is that a person's gratitude for another underscores the magnitude of the feelings of social distress, commitment, and satisfaction with others. 28,29 According to Heekerens et al, 30 the practice of cultivating gratitude also allows individuals to establish connections between their present life and future dreams, as well as to re ect on their relationships with signi cant others, whether family or friends.…”
Section: Discussionmentioning
confidence: 99%